Role of Imprinting Disorders in Short Children Born SGA and Silver-Russell Syndrome Spectrum - Fuke, Tomoko; Nakamura, Akie; Inoue, Takanobu; Kawashima, Sayaka; Hara, Kaori Isono; Matsubara, Keiko; Sano, Shinichiro; Yamazawa, Kazuki; Fukami, Maki; Ogata, Tsutomu; Kagami, Masayo (The journal of clinical endocrinology and metabolism, 2021)
Abstract Background (Epi)genetic disorders associated with small-for-gestational-age with short stature (SGA-SS) include imprinting disorders (IDs). Silver-Russell syndrome (SRS) is a representative ID in SGA-SS and has heterogenous (epi)genetic causes. Subjects and Methods To clarify the contribution of IDs to SGA-SS and the molecular and phenotypic spectrum of SRS, we recruited 269 patients with SGA-SS, consisting of 103 and 166 patients referred to us for genetic testing for SGA-SS and SRS, respectively. After excluding 20 patients with structural abnormalities detected by comparative genomic hybridization analysis using catalog array, 249 patients were classified into 3 subgroups based on the Netchine-Harbison clinical scoring system (NH-CSS), SRS diagnostic criteria. We screened various IDs by methylation analysis for differentially methylated regions (DMRs) related to known IDs. We also performed clinical analysis. Results These 249 patients with SGA-SS were classified into the “SRS-compatible group” (n = 148), the “non-SRS with normocephaly or relative macrocephaly at birth group” (non-SRS group) (n = 94), or the “non-SRS with relative microcephaly at birth group” (non-SRS with microcephaly group) (n = 7). The 44.6% of patients in the “SRS-compatible group,” 21.3% of patients in the “non-SRS group,” and 14.3% in the “non-SRS with microcephaly group” had various IDs. Loss of methylation of the H19/IGF2:intergenic-DMR and uniparental disomy chromosome 7, being major genetic causes of SRS, was detected in 30.4% of patients in the “SRS-compatible group” and in 13.8% of patients in the “non-SRS group.” Conclusion We clarified the contribution of IDs as (epi)genetic causes of SGA-SS and the molecular and phenotypic spectrum of SRS. Various IDs constitute underlying factors for SGA-SS, including SRS.